The transformation of portuguese foreign policy towards China during António Costa’s administrations (2015-2024) - Bastos da Silva, Flávio (REVISTA ELECTRONICA IBEROAMERICANA, 2025)
The establishment of diplomatic relations between Portugal and the People’s Republic of China (PRC) dates back to 1979, but it is rooted in a historical relationship spanning approximately 500 years. Over the past five decades, these relations have evolved through the expansion of cooperation into new domains, culminating in Portugal’s accession to the Belt and Road Initiative. This study aims to explore and analyse thetransformation of Portuguese foreign policy towards China during António Costa’s governments (2015–2024). Framed by Role Theory, the article examines Portugal’s role in the International System and its ability to balance economic interests with the expectations of its Western allies. Using a qualitative methodology that combines exploratory and interpretative methods, this study reveals a pragmatic and flexible evolution of Portugal’s foreign policy, reconciling strategic, commercial, and political interests without compromising its commitment to NATO and the European Union, thereby maintaining its international role.
Keywords: Portugal; China; Foreign Policy; Belt and Road Initiative; Role Theory